Upaya Meningkatkan Pemahamaan Konsep Bilangan Beserta Lambang Bilangan Pada Anak Usia Dini Usia 5-6 Tahun Melalui Media Kardus Modifikasi di TK Al Birru Arkan - Yulistia, Yulistia; Munajat, Asep; Ernawati, Elnawati (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
This research aims to improve the understanding of the concept of numbers and number symbols in early childhood, especially 5-6 years old, by using modified cardboard media as a learning aid. This media is designed to provide an interactive, engaging, and appropriate learning experience that is in accordance with the characteristics of early childhood development. The research method used is Classroom Action Research (PTK) which consists of two cycles, where each cycle includes planning, implementation, observation, and reflection stages. The subject of the study is Al Birru Arkan Kindergarten students in the age group of 5-6 years. Data collection techniques include observation, interviews, documentation, and number concept ability tests. The results of the study show that the application of modified cardboard media significantly improves children's understanding of the concept of numbers and number symbols. In cycle I, the average achievement of children's understanding reached 65%, while in cycle II it increased to 85%. The learning process involving modified cardboard media has also been proven to increase children's interest and motivation in learning, so that they are more active in participating in learning activities. The conclusion of this study is that modified cardboard media is effective in improving understanding of the concept of numbers and number symbols in early childhood. This media can be an innovative alternative for teachers in teaching basic mathematics material at the early childhood education level.